We Have All Been Warned: Public Debate on the Capitol Attack in Finland and Sweden - Malkki, Leena (Terrorism and political violence, 2021)
The Capitol attack has provoked intensive debate and reflection far beyond the United States. These debates and their repercussions will be part of the legacy of the event. The article looks at the public debate on the Capitol attack in Finland and Sweden. In both countries, the Capitol attack was interpreted as a warning about the powerful consequences of sowing distrust towards democracy. The attack may inspire far-right actors to attempt to shake the democratic system in these countries too. Whether such mobilisation could succeed and gain support from within the political system seems unlikely, but not entirely impossible.